Understanding Contemporary Vigilantism: A Case Study of the Vigilante Group of Nigeria (VGN) - Osakwe, Chukwuma C.C.; Audu, Bulus Nom (NIU Journal of Social Sciences; Vol 5 No 2 (2019): KIU Journal of Social Sciences, Vol. 5 No. 2, June 2019, 2019)
Vigilante groups in Nigeria assume different structures and patterns of operation and these are determined by the nature of their societies and the purpose for which they exist. Many of them that can be classified as militias represent interests along the plural Nigeria societies and religions. Yet there are other groups under the umbrella of the Vigilante Group of Nigeria (VGN) that do not represent any political, economic and religious interest, but only tackles crime in Nigerian communities. This group (VGN) is the focus of this paper. Thus, this paper examines a rare and interesting dimension of vigilantism in Nigeria by reviewing the VGN which was established; placing willing vigilante groups under one National umbrella, and later given Federal backing with the aim of operating professionally alongside government Law Enforcement agencies in the country. Examining the VGN as a single body in effect provides a concise and more encompassing understanding of vigilantism in Nigeria. However, as exist in other Law Enforcement Agencies in Nigeria, there is the chronic challenge of logistics and adequate funding in not just boosting operational efficiency but also enhancing capacity building and manpower development to majority of members who are still largely illiterate.